2007
DOI: 10.1037/0022-3514.93.6.1054
|View full text |Cite
|
Sign up to set email alerts
|

Early positive emotionality as a heterogenous trait: Implications for children's self-regulation.

Abstract: Young children's positive affect in scripted laboratory procedures and in free-flowing social interactions may reflect the activation of related but distinct aspects of positive emotionality (PE), with different implications for self-regulation. The authors observed children's PE in scripted laboratory procedures and in naturalistic interactions with mothers in 2 studies: at 9, 14, 22, 33, and 45 months (the Parent-Child Study, N=112) and at 7, 15, 25, 38, and 52 months (the Family Study, N=102). Measures of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 44 publications
3
76
0
Order By: Relevance
“…Indeed, temperament studies suggest that high surgency in children may negatively influence the development of effortful control. Consistent with this notion, Kochanska and colleagues [120] demonstrated that positive emotionality expressed during structured laboratory tasks, interpreted as reflecting strong approach tendencies, were negatively associated with performance on behavioral effortful control tasks. However, in studies examining working memory, extraversion is associated with better performance but only when there is a higher cognitive load [121].…”
Section: Extraversionmentioning
confidence: 80%
See 1 more Smart Citation
“…Indeed, temperament studies suggest that high surgency in children may negatively influence the development of effortful control. Consistent with this notion, Kochanska and colleagues [120] demonstrated that positive emotionality expressed during structured laboratory tasks, interpreted as reflecting strong approach tendencies, were negatively associated with performance on behavioral effortful control tasks. However, in studies examining working memory, extraversion is associated with better performance but only when there is a higher cognitive load [121].…”
Section: Extraversionmentioning
confidence: 80%
“…Children who are rated as more agreeable by their peers perform better on tasks requiring effortful behavioral regulation [148]. Notably, Kochanska and colleagues [120] demonstrated that positive emotionality expressed during mother-child interactions, interpreted as reflecting high affiliation, was positively associated with behavioral indices of effortful control.…”
Section: Agreeablenessmentioning
confidence: 97%
“…It will be of great interest to examine the degree to which particularly hot aspects of "effortful control," as measured by Kochanska, Aksan, Penney, and Doobay ( 2007 ), are similar to, or the same as, hot executive function as described in this chapter. Based on Kochanska's work, there may be substantial implications for individual differences in hot executive function as predictors of later rulebased moral behavior in children and adolescents, particularly males.…”
Section: Compliance and Moral Development In Young Childrenmentioning
confidence: 94%
“…Finally, longitudinal research has found some associations between positive emotions linked to approach motivation (such as joy) and impulsivity and reduced self-regulation ability among young children (Blair, Peters, & Granger, 2004; Kochanska, Aksan, Penney, & Doobay, 2007). These results suggest that at least some aspects of well-being may predict lower emotion regulation ability in the long-term.…”
Section: The Ability To Regulate Emotional Behavior and Well-being Anmentioning
confidence: 99%